SOME ASPECTS OF THE BIOLOGY OF TACHYSURUS TENUISPINIS DAY FROM VERAVAL - Raje, Sadashiv Gopal (Journal of Indian Fisheries Association, 2015)
The regression coefficients in length-weight relationship of males and females of Tachysurus tenuispinis differ significantly. The relative condition factor was calculated for females in relation to various lengths and months. The sex ratio in the catch varied widely in the different months. The number of eggs ranged from 72 to 89 for the fish of length 394 to 570 mm. Empty stomachs occurred in a very high percentage (63.5%) of the total stomachs examined. This is a bottom carnivorous feeder. The main food items found in the guts in order of preference were crustaceans, polychaetes, molluscs, fishes and echinoderms. Keywords: Tachysurus tenuispinis, length-weight relationship, relative condition factor, sex ratio, fecundity, food and feeding habit